The Role of Litotes in The Russian Language and Literature - Kazakbaeva Aziza (Global Scientific Publishing, 2023)
This article explores an artistic trope which is called litotes. The author wants to talk about the correct usage and application of this trope in literature and in daily life of Russian people, like, how litotes are used in fairy tales, in allegories and in poetry.
Keywords: litotes; Russian literature; trope; poetry